Rancang Bangun Sistem Pengukuran Medan Magnet Menggunakan LabVIEW, CONTROLLER NI cRIO-9022, dan DTM-151 Digital Teslameter - Musaffiriyan Rasyid Ghoni; Andi Dharmawan; Slamet Santosa (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2015)
Pusat Teknologi Akselerator dan Proses Bahan (PTAPB) BATAN Yogyakarta currently developing a magnetic field measurement system for cyclotron machine. Magnetic field measurement on cyclotron is required to determine the magnitude and direction of the magnetic field. The system used LabVIEW to create an interface application (HMI) and system programming. The control function implemented by using controller NI cRIO-9022 combined with NI 9512 module, which would controlling the motion component, that isthe stepper motor. The acquisition data function implemented by using DTM-151 Digital Teslameter to measure the magnetic field. The measurement works within the cartesian coordinate plane (x,y). A permanent magnet was used as the measurement trial object. The size of the magnet was smaller than measurement dimension of the system therefore the measurement dimension of the magnetic plane was made with the size of (100 x 100) mm. The initial position coordinate of the teslameter 1 and teslameter 2, respectively, set at (430,720) and (430,240). The trial was excuted 2 times (2 different magnet position). Each trial consist of 3 times measurement, so there’s 6 data file obtained. On those data file, there’s an average of 1.117 data on each file. The motor speed was set on 25 mm/s. The data reading speed was set on 10 data/s, which would caused a 2,5 mm interval on one single data.